MEMBANGUN PENDIDIKAN ISLAM BERBASIS MODERASI DI INDONESIA - Dozan, Wely; Abdul Karim, Sya’ban (Jurnal El-Hikam, 2023)
The dynamics of the epistemology of Islamic education knowledge has become an outline theme to be developed continuously by Muslim scholars and Islamic thinkers, namely by making contributions and formulating various theories to build the true face of Islamic education. Problems with education become the mainstream to be considered for teachers to students to explore creativity, innovation, and related matters, namely education as one of the transformations so that it is realized optimally. Especially in Indonesia, in education today, we still find problems and conflicts in schools that continue to this day. Especially in the social aspect, and the lack of optimization of moderation-based teachings in Islam. This is one of the concrete evidences, namely brawls occur between fellow students, students do not respect teachers, the lack of tolerance possessed by students, even sometimes teachers are hard on students, and several other conflicts occur, especially in Islamic education. This Asusmi has become the center of attention, especially for Islamic education to build moderation-based learning so that it is an effort to minimize conflicts that occur in the world of Islamic education, especially those developing in Indonesia. The focus of this research is to answer several issues that are quite urgent, namely how the face of moderation-based Islamic education (Wasthiyyah) in Indonesia.